Assessment of the level of transformation of information support for public finance management - S.V.; S.V.; V.M. (Економіка, управління та адміністрування)
In the conditions of a war of liberation, the issues of financing defense capabilities and ensuring the fulfillment of social functions of the state are extremely complicated. For this reason, the primary task is to achieve the most efficient management of public finances, a significant part of which is the financial assistance of the governments of the democratic countries of the world and international financial organizations. It was established that the prolongation of international financial aid can take place only under the conditions of implementation of the strategy of reforming the system of public finance management, transformation of the system of state financial control, improvement of the accounting system in the public sector. The state of legal regulation of accounting and financial reporting by public sector entities is determined, the compliance of national regulations (standards) of accounting in the public sector with international accounting standards of the public sector is determined, certain shortcomings of legal regulation are identified and measures, the implementation of which will ensure complete and high-quality modernization of the accounting and financial reporting system in the public sector.